PEMANFAATAN KELOPAK BUNGA ROSELA SEBAGAI PEWARNA DALAM PEMBUATAN VELVA BUAH NIPAH - Budi; Evy Rossi; Usman Pato (Fakultas Pertanian Universitas Riau, 2023)
This study aimed to obtain the best formulation in the manufacture of velva made from nipah fruit combined with rosella flower petals. This research was conducted experimentally using a completely randomized design (CRD) of four treatments and four replications. The treatments in this study were the ratio of nipa palm pulp (N) to rosella flower petal pulp (R), namely NR1 = 90:10 (w/w), NR2 = 80:20 (w/w), NR3 = 70:30 (w/w), and NR4 = 60:40 (w/w). The results were statistically analyzed using Analysis of Variance (ANOVA). The results showed that the ratio of nipa palm pulp: to rosella petal pulp significantly affected crude fiber content, acidity, and velva melting time. The results also showed that the treatment affected the velva sensory test parameters, including color, aroma, and taste. Meanwhile, the difference in the ratio of nipa palm pulp: to rosella petal pulp had no significant effect (P>0.05) on the softness of the velva. The hedonic sensory test showed that the ratio of nipah fruit and rosella had a significant effect (P<0.05) on overall velva acceptance. Based on chemical analysis and velva sensory test, the treatment selected in this study was the ratio of nipah fruit pulp to rosella flower pulp 70:30 (NR3) with a fiber content of 1.90%, overrun 30.32%, and acidity 4.70. The velva melting time was 9.10 m, and the sensory assessment had a red color (2.50), soft texture (3.80), slightly fragrant with nipah fruit (2.70), and slightly tasted like nipah fruit (2.60), and overall acceptance liked by panelists (4.40).